BTNL8 is Expressed by Human Mreg-induced FOXP3+ iTregs. (July 2018) - Riquelme, Paloma; Schlitt, Hans J.; Geissler, Edward K.; Hutchinson, James A.
Abstract : Introduction: The human regulatory macrophage (Mreg) has emerged as a promising cell-based adjunct immunosuppressive therapy and is currently being investigated in a Phase-I/II trial as a means of safely reducing maintenance immunosuppression in living-donor kidney transplant recipients. Exposing naïve human CD4 + T cells to allogeneic Mreg in co-culture led to their conversion into IL-10-producing FoxP3 + Tregs capable of suppressing polyclonally-stimulated T cell proliferation. These Mreg-induced Tregs exhibited typical characteristics of human iTreg, including cell-surface expression of GARP, LAP and CD121a/b, low levels of TSDR demethylation, and absence of Helios expression. To discover novel, unique markers of Mreg-induced iTregs, whole-genome gene expression profiling studies were performed, which led to identification of butyrophilin-like 8 (BTNL8). Methods: A microarray dataset was generated comprising 5 replicates of 4 human cell types – namely, (1) flow-sorted fresh CD4 + T cells, (2) CD4 + T cells after 5-day coculture with allogeneic human Mregs, (3) CD4 + T cells after control macrophage co-culture, and (4) CD4 + T cells cultured alone for 5 days. BTNL8 expression in T cells was investigated by q-PCR, immunoblotting and flow cytometry. Results: BTNL8 stood out as a highly discriminatory marker of Mreg-generated iTregs with likely immunological relevance. BTNL8 is a little-studied Ig-superfamily (IgSF) receptor belonging to the four-member butyrophilin-like (BTNL) gene family in humans, which is closely related to the butyrophilin (BTN) family, both of which families are structurally and functionally related to the B7-costimulatory molecules. Recent studies implicate members of the BTN family in controlling regulatory T cell responses; however, it was previously reported that BTNL8 is not expressed by T cells. Up-regulation of BTNL8 mRNA in Mreg-cocultured T cells was corroborated by qPCR using primers amplifying both the BTN-like and B7-like variants of BTNL8. By sequencing, it was shown that Mreg-cocultured T cells expressed only the B7-like variant. BTNL8 was quantified in CD4 + CD25 + CD127 int Treg and non-Treg from blood. BTNL8 was not reliably detected in freshly-isolated Tregs or non-Treg; however, stimulation with PHA strongly induced BTNL8 expression in Tregs and more weakly in non-Treg. Immunoblotting revealed stronger expression of the B7-like (37kD) isoform of BTNL8 in Mreg-cocultured CD4+ T cells than controls. By flow cytometry, stronger BTNL8 expression was found in Mreg-induced iTregs compared to CD25 + FoxP3 - or CD25 - non-Tregs. Addition of 10 μg/ml BTNL8-Fc fusion protein to allogeneic cocultures of Mregs and naïve CD4 + T cells led to a small, but consistent increase in iTreg generation. Conclusion: Taken together, these results indicate that BTNL8 is more highly expressed in activated Treg than non-activated Treg or non-Treg. Therefore, the 37-kD variant of BTNL8 may be a useful marker of human activated, Mreg-induced Treg.